PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA PADA GEDUNG GEREJA GMIM PNIEL BAHU - Novellia Anise; Benny Maluegha; Hengky Luntungan (JURNAL POROS TEKNIK MESIN UNSRAT, 2021)
This research aims to make simple technical planning of Solar Power Plant system to meet the electricity needs of GMIM Pniel Bahu Church building. This research was carried out in several stages, namely literature studies, data collection, data processing, analysis and discussion, and most recently conclusions.            The data required in this study are data on the use of electrical equipment obtained directly at the research site, as well as radiation data and clearness index manado city obtained from NASA Surface Meteorology and Solar Energy database. Data processing is done using HOMER(R) 2.86 software.Result simulation with homer software(R) 2.86   for on-grid system shows that    for on-grid system, electricity needs of GMIM Pniel Bahu Church building are met by PLN network of 31,529 kWh/year (99%) and PLTS of 170 kWh/year (1%). The PLTS used consists of a 0.1 kW PV and a 0.1 kW converter. As for the off-grid system, the power supply for gmim pniel bahu church building is provided by PLTS consisting of 30 kW PV, 208 pieces of Trojan T-105 battery and 15 kW converter capable of producing electrical energy of 51,107 kWh/year.